A methodology for estimating the impact of aircraft carrier operational cycles on the maintenance industrial base - Yardley, Roland J.; Schank, John F. (John Frederic), 1946-; Kallimani, James G.; Raman, Raj.; Grammich, Clifford A. (Clifford Anthony), 1963-; National Defense Research Institute (U.S.). Acquisition and Technology Policy Center; Rand Corporation; United States. Navy. (Santa Monica, CA : RAND, 2007)
The U.S. Navy has implemented the Fleet Response Plan (FRP), which provides for an increased surge capability by Carrier Strike Groups. Although regularly scheduled six-month deployments still occur, aircraft carriers achieve a high state of readiness early and sustain the readiness for a longer period. This increased readiness provides the Navy with a more responsive aircraft carrier fleet and with the ability to employ aircraft carriers more flexibly. The analysis focused on the demands of ten Nimitz-class carriers, which will be in operation over the next two decades. We used a model based on the supply of and demand for workers at the primary naval shipyards that service aircraft carriers, to estimate the magnitude and timing of work (demand). The modeling used naval shipyard-provided data that forecast the supply of workers and maintenance demands of aircraft carriers and all other ships. We varied the aircraft carrier maintenance cycles and size of work packages to focus on the effects that they would have on the demand for workers at Norfolk Naval Shipyard and Puget Sound Naval Shipyard and Intermediate Maintenance Facility. The Program Executive Office for Aircraft Carriers tasked the RAND Corporation to examine the effect of the extension of time between depot maintenance availabilities, the increased use of continuous-maintenance periods, and the potential reductions in the size of the aircraft carrier fleet on the industrial base for aircraft carrier maintenance-the public and private shipyards and depots that maintain and repair aircraft carriers. The modeling revealed that increasing carrier maintenance-cycle length can reduce the number of carriers in maintenance and make more carriers available to deploy or surge. However, implementing longer cycles must be timed carefully to prevent problems in managing the workforce of the maintenance industrial base. This report should be of interest to persons concerned with the operational availability and readiness of Navy aircraft carriers under the Fleet Response Plan, including those in the Naval Sea Systems Command (NAVSEA), the Fleet Forces Command, and the Type Commanders.
Introduction -- Overview of aircraft carrier maintenance and FRP cycles -- Modeling the maintenance industrial base -- Development and analysis of alternative maintenance strategies -- Effects on the industrial base -- Effects on operational availability -- Summary and concluding observations -- Appendix A: The one shipyard concept -- Appendix B: Mapping of trade skills -- Appendix C: Other work performed at naval shipyards -- Appendix D: Evaluation of supply and demand for representative trade skills.
"RAND National Defense Research Institute."
"This research was conducted within the Acquisition and Technology Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 71-72).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Navy -- Operational readiness; Aircraft carriers -- United States -- Maintenance and repair; Naval strategy; Queuing theory; United States -- Military policy